EVALUASI TEKNOLOGI AIR MINUM ISI ULANG DI DKI JAKARTA - Yudo, Satmoko; Rahardjo, Petrus Nugro (Center for Environmental Technology, 2005)
Ã‚Â Nowadays raw water resources for drinking water are less and less available, especially in Jakarta. For example, the condition of most rivers in Jakarta is extremely polluted by wastewaters, such as domestic and industrial wastewater. Some of industrial wastewater straightly discharged into the rivers are classified asÃ‚Â toxic and hazardous wastewater.Ã‚Â Therefore all rivers in Jakarta are not feasible to be used as the raw water for clean water treatment processes. Even ground water is not already safe to be used as the raw water for drinking water, because it has commonly been contaminated by seepage of septic tanks and polluted surface waters. Because of that, many people living in Jakarta tried to find other alternatives. Commercially sold mineral water is one good option for supplying drinking water need, but the prices are relatively expensive for most of people.There were more than 1,000 refill drinking water depots growing in the last ten years. They are one of the best answers to many people, but the quality of drinking water is still debatable. In other word, there is not a standard regulation for the water treatment processes, so the depots cannot guarantee that the produced water already fulfill the quality standard of drinking water. In order to give a good service for community living in Jakarta, it is very important to evaluate all aspects of technology, management and services. Ã‚Â Keywords : Refill drinking water technology, water treatment processes.